2004
DOI: 10.1097/01.asn.0000135115.63412.a9
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and the Renal Epithelial Transport and Toxicity of Inorganic Mercury

Abstract: Abstract. The epithelial cells that line the renal proximal tubule have been shown to be the primary cellular targets where mercuric ions gain entry, accumulate, and induce pathologic effects in vivo. Recent data have implicated at least one of the organic anion transport systems in the basolateral uptake of inorganic mercury (Hg). With the use of a line of type II MDCK cells transfected stably with the human organic anion transporter 1 (hOAT1), the hypothesis that hOAT1 can transport mercuric conjugates of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…A similar interaction with rOat3 and mercury N-acetylcysteine conjugates is also seen in Xenopus oocytes (Aslamkhan et al 2003). Subsequently, similar findings were made for conjugates with the sulfhydryl-containing amino acid homocysteine (Zalups and Ahmad 2004). Methylmercury is also conjugated with homocysteine and taken up into MDCK cells expressing hOAT1 (Zalups and Ahmad 2005).…”
Section: Determinants Of Transport Efficacysupporting
confidence: 58%
“…A similar interaction with rOat3 and mercury N-acetylcysteine conjugates is also seen in Xenopus oocytes (Aslamkhan et al 2003). Subsequently, similar findings were made for conjugates with the sulfhydryl-containing amino acid homocysteine (Zalups and Ahmad 2004). Methylmercury is also conjugated with homocysteine and taken up into MDCK cells expressing hOAT1 (Zalups and Ahmad 2005).…”
Section: Determinants Of Transport Efficacysupporting
confidence: 58%
“…Of these conjugates, only Cys-SHg-S-Cys and Hcy-S-Hg-S-Hcy appear to be taken up by ARPE-19 cells. Similarly, these two conjugates have been identified as transportable forms of Hg 2+ in other cell-types (Aslamkhan et al, 2003;Zalups and Ahmad, 2004;. Moreover, the majority of the transport of these conjugates by RPE cells appears to require the presence of Na + .…”
Section: Discussionmentioning
confidence: 97%
“…MeAIB and PAH are classic inhibitors of system A and the organic anion transporter (OAT1 and OAT3), respectively. System A has not been identified as a mechanism for the transport of mercuric compounds (Cannon et al, 2001) while OAT has been shown to transport several conjugates of Hg 2+ and CH 3 Hg +, (Aslamkhan et al, 2003;Zalups and Ahmad, 2004,2005a,2005b. In addition, some cells were exposed to Cys-S-[ 203 Hg]-S-Cys or Hcy-S-[ 203 Hg]-S-Hcy in the presence of a combination of two unlabeled amino acids (methionine and lysine, methionine and cysteine, methionine and arginine, alanine and cysteine, arginine and cysteine, or lysine and cysteine).…”
Section: Evaluation Of Transportmentioning
confidence: 99%
“…For example, mercury exists in the blood in thiol conjugates (with glutathione and cystathione), which effectively act like organic anions. OAT1 and OAT3 appear to be the major transporters involved in elimination of mercuric conjugates, which can lead to renal and central nervous system toxicity following mercurial exposure (48)(49)(50)(51). The proximal tubule of the kidney of the Oat1 knockout mouse is largely resistant to nephrotoxic damage that occurs from systemic administration of mercuric chloride (Figure 3) (52).…”
Section: Drugs and Toxinsmentioning
confidence: 99%